Graphene Formation through Pulsed Wire Discharge of Graphite Strips in Water: Exfoliation Mechanism - Shigeru Tanaka (Nanomaterials, 2021)
This study aims to clarify the mechanism of exfoliation of graphene through electrical pulsed wire discharge (PWD) of a graphite strip, made by the compression of inexpensive expanded graphite in water. The explosion of the graphite strip was visualized using a high-speed video camera. During the energized heating of the sample, explosions, accompanied by shock waves due to expansion of gas inside the sample, occurred at various locations of the sample, and the sample started to expand rapidly. The exfoliated graphene was observed as a region with low light transmittance. The PWD phenomenon of graphite strips, a type of porous material, is reasonably explained by the change in electrical resistivity of the sample during discharge and the light emission due to energy transition of the excited gas.